Predictors of the perceived risk of COVID-19 and adherence to confinement guidelines in the context of the COVID-19 pandemic. (13th April 2021) - Jarego, M.; Rodríguez, E.; Ciaramella, A.; Miró, J.; Pais-Ribeiro, J.
Abstract : Introduction: Complete adherence to public health guidelines is essential to reduce the spread of COVID-19. Studies on the factors associated with increased/decreased adherence to these measures have the potential to inform public policies directed at increasing adherence, and thus helping to control the spread of the current pandemic. Objectives: This study aimed at assessing the demographic and psychosocial predictors of the perceived risk of the COVID-19 and adherence to confinement guidelines during the first mandatory lockdown in Portugal. Methods: A convenience sample of 430 adults living in Portugal between March 19 th and May 2 nd, 2020 completed an online survey asking participants about the perceived risk of the COVID-19 and adherence to confinement guidelines. Participants also completed a sociodemographic questionnaire and measures of psychological function. Multiple regression analysis was performed. Results: Teleworking and Risk and COVID-19 controllability were significant predictors of the perceived risk of COVID-19 as measured by the perceived risk of being infected with COVID-19. Teleworking participants and those perceiving COVID-19 as less controllable reported a higher perceived risk of being infected with COVID-19 than those who were not in telework and perceived COVID-19 as a controllable condition. Adherence to confinement guidelines was predicted by the mental health status and perceived risk of COVID-19. Participants who reported worse mental health status, who perceived COVID-19 as a dangerous condition, and who trusted the public health system reported greater adherence to confinement guidelines. Conclusions: The results of this study will be discussed considering their implications to public health policymaking to promote adherence to public health policies. Disclosure: No significant relationships.